En qué punto se encuentra el acceso abierto. Cómo medirlo - Gargiulo, Paola (Anuario ThinkEPI, 2015)
Reseña de tres informes: Â Archambault, Eric;Â Amyot, Didier;Â Deschamps, Philippe;Â Nicol, Aurore;Â Rebout, Lise; Roberge, Guillaume (2013). Proportion of open access peer reviewed papers at European level and worldwide - 2004-2011. European Commission DG Research; Innovation Science-Metrix Inc. http://www.science-metrix.com/pdf/SM_EC_OA_Availability_2004-2011.pdf Â Caruso, Julie;Â Nicol, Aurore;Â Archambault, í‰ric (2013). Open access strategies in the European Research Area. European Commission DG Research & Innovation Science-Metrix Inc. http://www.science-metrix.com/pdf/SM_EC_OA_Policies.pdf Â Nicol, Aurore;Â Caruso, Julie;Â Archambault, í‰ric (2013). Open data policies and strategies in the European Research Area and beyond. European Commission DG Research; Innovation Science-Metrix Inc. http://www.science-metrix.com/pdf/SM_EC_OA_Data.pdf